Primary Orbital Teratoma with Tooth in an Adult: A Rare Association with Cataract and Corectopia*. (29th July 2013) - Singh, Manpreet; Singh, Usha; Gupta, Adit; Zadeng, Zoramthara
Abstract: Introduction : Orbital teratoma is a known cause of proptosis in neonates but it is rare in adults. Case report : An adult female presented with primary orbital teratoma with a well formed tooth inside the multicystic mass. Anterior orbitotomy with cyst excision was done with retrieval of a canine tooth. Comment : This report documents a unique case of orbital teratoma presenting in an adult with well formed canine tooth inside. Microcornea, corectopia and cataract were other distinctive coexisting features of our case.